English Immersion at Modern Pesantren: Communities of Practice and SLA Perspective - Nur Alfa Rahmah; Syamsul Hadi (Universitas Islam Negeri Antasari Banjarmasin, South Kalimantan, Indonesia, 2025)
This study explores the English immersion practice at Pondok Pesantren Darul Hijrah Putri in South Kalimantan through the lens of Communities of Practice (CoP) and Second Language Acquisition (SLA) theories. Drawing on qualitative data from interviews with students and teachers, institutional documents, field observations, and transcribed student conversations, the research uncovers how immersive language practices are organically built and sustained within a unique religious educational community. The findings reveal that English use is maintained not only through formal curriculum and institutional structures but also through peer participation, leadership modeling, and internalized social norms. Students experience language acquisition not merely as academic achievement but as part of their religious identity and social belonging, fostering strong engagement and functional fluency. It portrays how language practice is embraced in the sociolinguistic setting of pesantren as a community of practice. Some limitations, such as fossilized errors, limited authentic input, and affective barriers, are also discussed. In the end, this study offers theoretical and practical implications for the design of immersion in socio-religious educational settings.